Minocycline Alone and in Combination with Polymyxin B, Meropenem, and Sulbactam against Carbapenem-Susceptible and -Resistant Acinetobacter baumannii in an In Vitro Pharmacodynamic Model - Beganovic, Maya (Antimicrob Agents Chemother, 2021)
Acinetobacter baumannii is recognized as an urgent public health threat by the Centers for Disease Control and Prevention (CDC). Current treatment options are scarce, particularly against carbapenem-resistant Acinetobacter baumannii (CRAB). We simulated the impact of minocycline standard (200 mg load + 100 mg Q12h) and high (700 mg load + 350 mg Q12h) doses, polymyxin B (2.5 mg/kg Q12h), sulbactam (1 g Q6h and 9 g/24 h as continuous infusion), and meropenem (intermittent 1 or 2 g Q8h and 6 g/24 h as continuous infusion) alone or in combination against CRAB and non-CRAB isolates by simulating human therapeutic dosing regimens in a 72-h, in vitro pharmacodynamic (IVPD) model. There were no monotherapy regimens that demonstrated bactericidal activity against the tested non-CRAB and CRAB strains. Resistance development was common in monotherapy regimens. Against the CRAB isolate, the triple combination of high-dose minocycline (fAUC/MIC 21.2), polymyxin B (fAUC/MIC 15.6), and continuous-infusion sulbactam (67% T(>MIC)) was the most consistently active regimen. Against non-CRAB, the triple therapy regimen of high-dose minocycline (fAUC/MIC 84.8) with continuous-infusion meropenem (100% T(>MIC)) and continuous-infusion sulbactam (83% T(>MIC)), as well as the double therapy of high-dose minocycline (fAUC/MIC 84.8) with continuous-infusion meropenem (100% T(>MIC)), resulted in persistently bactericidal activity. In conclusion, triple therapy with high-dose minocycline, continuous-infusion sulbactam, and polymyxin B produced the most significant kill against the carbapenem-resistant Acinetobacter baumannii, with no regrowth and minimal resistance development.